A comparative study on selected antioxidants during pollination induced senescence on Dendrobium Sonia and Dendrobium Savin White - Rebecca, O.P.S.; Zuliana, R.; Wijenthiran, K.; Boyce, A.N.; Chandran, S. (2008)
Dendrobium Sonia and Dendrobium Savin White are popular Dendrobium hybrids in the Orchidaceae Family which are ethylene-sensitive and exhibit earlier senescence due to pollination. Pollinated Dendrobium Sonia and Dendrobium Savin White showed shorter vase life and initiate earlier perianth senescence that demonstrates rapid sepal and petal wilting and discolouration. Experiments were carried out to observe the changes in antioxidant activities and pigment fading throughout the flower's vase life. As Dendrobium Sonia and Dendrobium Savin White senesces, there is discolouration, the flower appears dull and weak, which indicates pigment loss and this observation is correlated with the L* a*/b* colour readings carried out using the Chromameter CR-200. The total anthocyanin quantification using the pH-differential method showed that polllinated Dendrobium Sonia had lower concentration compared to unpollinated Dendrobium Sonia. The total polyphenol assay on pollinated and unpollinated flowers for both hybrids showed lower content in those pollinated compared to those unpollinated. The reducing power assay confirmed that there were antioxidant properties present in both hybrids and the reducing capability increases with the increase of dry weight sample. Â© 2008 Asian Network for Scientific Information.